2002
DOI: 10.1088/0022-3727/35/22/307
|View full text |Cite
|
Sign up to set email alerts
|

Plume splitting and sharpening in laser-produced aluminium plasma

Abstract: Plume splitting and sharpening were observed in laser-produced aluminium plasma created using 532 nm, 8 ns pulses from a frequency doubled Nd : YAG laser. Measurements were made using 2 ns gated fast photography as well as space and time resolved optical emission spectroscopy. The motion of the leading edge of the plume was studied with several background air pressures and the expansion of the plume front was compared with various expansion models. Combining imaging together with time resolved emission diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
52
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(59 citation statements)
references
References 19 publications
7
52
0
Order By: Relevance
“…9,28 This spatial splitting of the plume is entirely different from plume splitting observed previously using time of flight emission spectroscopy where a part of the plume species penetrated into the ambient region while the other part slowed down due to a collision with background gas. 10,12 This spatial splitting has been observed irrespective of the spot size used in the present studies. Plume splitting phenomena are evident in the images recorded with a 280 m spot size at times greater than 1 s where a part of the leading edge of the plume detached from the bulk region.…”
Section: Resultssupporting
confidence: 59%
See 2 more Smart Citations
“…9,28 This spatial splitting of the plume is entirely different from plume splitting observed previously using time of flight emission spectroscopy where a part of the plume species penetrated into the ambient region while the other part slowed down due to a collision with background gas. 10,12 This spatial splitting has been observed irrespective of the spot size used in the present studies. Plume splitting phenomena are evident in the images recorded with a 280 m spot size at times greater than 1 s where a part of the leading edge of the plume detached from the bulk region.…”
Section: Resultssupporting
confidence: 59%
“…The plume expansion in vacuum can be described as self-similar and adiabatic and is treated well by Anisimov et al 8 Compared to plume expansion in vacuum; the interaction of the plume with an ambient gas is a far more complex gas dynamic process that involves deceleration, attenuation, and thermalization of the ablated species, as well as the formation of shock waves. [9][10][11][12] Our previous studies revealed a complex plume splitting in a laser created aluminum plasma expanding into an ambient environment where gas phase collisions transformed the initial temporal distribution into a very different final distribution. 12 We distinguished three distinct pressure regimes using fast photography, each of which is characterized by particular behavior of the plume.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such double-structures are often reported in the literature for both fs-and ns-laser ablation, being observed for plume propagating in an ambient gas [14,15,20,88] and in vacuum for high-fluence irradiation [56,57,67,75]. Reports from literature usually present a difference of one order of magnitude between the expansion velocities of the two plasma components.…”
Section: Resultsmentioning
confidence: 76%
“…Another characteristic phenomenon observed in laser-produced plasma expanding in low pressure background gas is the generation of successive plasma fronts or plume splitting. 5,19,[38][39][40][41] This is due either to double vaporization of target material from a relatively long duration laser pulse or to the formation of a double layer at the initially expanding plasma resulting from inter-penetration of the plasma species and background gas, which leads to plume splitting and sharpening. 39,40 As plume splitting is not observed in vacuum background, our observation of two successive plasma fronts in the presence of the magnetic field, seen in figure 5, might be ascribed to the existence of a strong field gradient very close to the target surface, which reduces plasma expansion rate due a reduction in the diffusion coefficient, thus providing similar interaction conditions to those in low pressure background.…”
Section: Aip Advances 7 085002 (2017)mentioning
confidence: 99%